If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -0.4 = 5.2 Reorder the terms: -0.4 + X = 5.2 Solving -0.4 + X = 5.2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '0.4' to each side of the equation. -0.4 + 0.4 + X = 5.2 + 0.4 Combine like terms: -0.4 + 0.4 = 0.0 0.0 + X = 5.2 + 0.4 X = 5.2 + 0.4 Combine like terms: 5.2 + 0.4 = 5.6 X = 5.6 Simplifying X = 5.6
| 4x+2-(x-3)=0 | | 3(2a-1)=5 | | 4(5y-2)= | | 3x/4+1/2=1/4 | | 2(3a+1)=7 | | 3d-4-5d=7+d | | 8(3x+2)-4x=6 | | 8x+42b+544z=1000 | | 8x+2y=242 | | (2,8)5/2= | | 3a-(4b+2a)+5b= | | 3x^5-12x^4-45x^3+180x^2-48x+192=0 | | A=sw+w*w | | 5x-7+3x=7x-10 | | 5j+10=5 | | (9x^2+8x-2)+(-5x^2-7x+3)= | | 10x-5=12+6x | | P+0.02p=142.8 | | 25(xsqured-9)=25(x-3)(x+3) | | 8(3n+5)=8(9n+9)+6 | | In(x)=20 | | x+x*0.14=500 | | C=a+(n-8)dforn | | -6x-1=-6 | | 42/0.5= | | 2a+7=5a+9 | | 10r^2-2r=-4r+6 | | (x-6)*(x-6)=(x*x)-396 | | 45=2y | | 5x+43-2(x+7)=88-2x | | 0.16(y-2)+0.12y=0.20y-0.7 | | x^2-17X+3=0 |